Array-aided single-differenced satellite phase bias determination: Methodology and results - Khodabandeh, Amir (Institute of Navigation, 2014)
Integer ambiguity resolution at a single GNSS receiver gets feasible, if network-derived satellite phase biases (SPBs), among other corrections, are a-priori available. In this paper, the concept of array-aided between-satellite single-differenced (SD) SPB determination is introduced which is aimed to reduce the code-dominated precision of SD-SPB corrections. The underlying model is realized by giving the role of the local reference network to an array of antennas, mounted on rigid platforms, that are separated by a few meters only. A closed-form expression of the array-aided SD-SPB corrections is presented, thereby proposing a simple strategy to compute the SD- SPBs. Upon resolving double-differenced ambiguities of the array's data, the variance of the SD-SPB corrections is shown to be reduced by a factor equal to the number of antennas. This improvement in precision is also affirmed by numerical results. Experimental results demonstrate that the user's integer-recovered ambiguities converge to integers faster, upon increasing the number of antennas aiding the SD-SPB corrections. Integrated with the ionospheric corrections, the stated SD-SPB corrections carry over the precision improvement to the user's position as well.